2000
DOI: 10.1557/proc-659-ii10.3
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization of Nickel and Ni Alloy Substrates for YBCO Coated Conductors

Abstract: To avoid grain boundary grooving and abnormal grain growth during recrystallization of nickel and Ni alloy substrate tapes, the commonly used high recrystallization temperatures must be lowered.The development of the cube orientation is a nucleation-growth process. So the kinetics of the cube recristallization is strongly temperature dependent, and there is a very marked effect of the stacking fault energy (SFE) of the specific alloy on the activation energy. Concurrently with measurements of the formation kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…It is commonly accepted that a sharp cube recrystallization texture usually forms in materials with a large component of the copper-type rolling texture, in which the major components are S and C, whereas the cube texture does not form in materials with brass-type rolling texture, in which B is the major component. [22] Lu¨cke and Hirsch [23,24] suggested that cube grains have the best chance of growing because the cube orientation forms a 40 deg/<111> high mobility boundary with the major components of the deformation texture. For example, the S component best meets the condition to form 40 deg/<111> high mobility boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly accepted that a sharp cube recrystallization texture usually forms in materials with a large component of the copper-type rolling texture, in which the major components are S and C, whereas the cube texture does not form in materials with brass-type rolling texture, in which B is the major component. [22] Lu¨cke and Hirsch [23,24] suggested that cube grains have the best chance of growing because the cube orientation forms a 40 deg/<111> high mobility boundary with the major components of the deformation texture. For example, the S component best meets the condition to form 40 deg/<111> high mobility boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Ignoring the energy differences of the different grain boundaries, their model predicts that cube grains with less than six grain boundaries shrink slowly, and non-cube grains with less than six boundaries shrink rapidly, while non-cube grains with more than six boundaries will grow swiftly. Initially, this leads to strengthening of the cube-texture as the small non-cube grains disappear, as has been observed experimentally in both high-purity nickel [16][17][18][19][20] and aluminum alloys [36]. The resulting microstructure has a few large noncube grains with high-mobility boundaries in a fine-grained, cube-oriented matrix.…”
Section: Columnar Grain Growth Mechanismmentioning
confidence: 59%
“…It is worth noting that several studies have shown that a cube texture results from primary recrystallization of heavily cold-rolled, high-purity nickel [11][12][13][15][16][17][18][19][20][21][22]. The 90% thickness reduction used here is almost the minimum to obtain cube texture in primary recrystallization of nickel [20,21,22]. Therefore, weak cube textures were produced at all directional annealing speeds.…”
Section: Primary Directional Recrystallizationmentioning
confidence: 91%
See 2 more Smart Citations